Model Assessment of Biogeochemical Controls on Dissolved Organic Carbon Partitioning in an Acid Organic Soil - Lumsdon, David G; Stutter, Marc I; Cooper, Richard J; Manson, John R (Environmental science & technology, 2005)
A chemical model (constructed in the ORCHESTRA modeling framework) of an organic soil horizon was used to describe soil solution data (10 cm depth) and assess if seasonal variations in soil solution dissolved organic carbon (DOC) could be explained by purely abiotic (geochemical controls) mechanisms or whether factors related to biological activity are needed. The NICA-Donnan equation is used to describe the competitive binding of protons and cations and the charge on soil organic matter. Controls on organic matter solubility are surface charge and a parameter, γ, that accounts for the distribution of humic molecules between hydrophobic and hydrophilic fractions. Calculations show that the variations in solute chemistry alone are not sufficient to account for the observed variations of DOC, but factors that alter γ, such as biological activity, are. Assuming that DOC in organic soils is derived from soluble humic material and that γ is modified seasonally due to biological activity (with monthly soil temperature used as a surrogate for biological activity) we are able to model the observed seasonality of soil solution DOC over a 10-year period. Furthermore, with modeled DOC coupled to other geochemical processes we also model soil solution pH and Al concentrations.